KLEINE–LEVIN SYNDROME AFTER USE OF RECREATIONAL DRUGS - E. I. Semenova; Yu. V. Tokareva; Yu. A. Belova; A. S. Kotov; Yu. V. Eliseev (Русский журнал детской неврологии, 2015)
Kleine–Levin syndrome (KLS) is characterized by sleep attacks lasting several hours or days with imperative onset and awakening difficulty. The syndrome belongs to rare and little studied diseases not only in our country, but also throughout the world. It was first described in 1786. The diagnostic criteria for KLS include: 1) complaints of excessive somnolence; 2) sleepiness episodes lasting at least 18 hours daily; 3) at least 1–2 annual hypersomnia episodes lasting 3 days to 3 weeks; 4) predominance generally in adolescent males; 5) characteristic changes at polysomnographic study; 6) no relationship of hypersomnia to other somatic or mental disorders, such as epilepsy or depression; 7) no association with other sleep disorders, such as narcolepsy, sleep apnea, or nocturnal myoclonus. The etiology of the syndrome remains unknown. The disease may occur in the presence of trauma, metabolic disturbances, and other diseases. The likely etiology is considered to be viral or postinfection autoimmune encephalitis involving chiefly the hypothalamus. No specific treatment for KLS has been developed at present.The authors consider the historical description of the syndrome, its presumed etiology, pathogenesis, and clinical manifestations, including the results of additional studies. They describe their observed clinical case of KLS that manifested itself as hypersomnia, hyperphagia, and psychopathic disorders and developed when using amphetamine and cannabinoids for the treatment of traumatic brain injury